FULL DAY SCHOOL: REALISASI PEMBENTUKAN KARAKTER ANAK - Yuwono, Tristiyo Hendro (Jurnal Pendidikan Guru, 2017)
Efforts character formation of students in the face of contemporary life into educational challenge. Various community environmental problems regarding juvenile delinquency make anxiety for families, schools and communities. To respond to this need educational institutions that contributed to the formation of student character. Schools that implement the values of religion in the curriculum and the learning will make the conditioning and training for the student to improve his character. Full day school system is a full day school designed to give a quality learning, form the character better learners by habituation given, as well as the achievements obtained more leverage and quality. Interest full day school education system is to provide a solid foundation to develop and improve Intelligence Quotient (IQ), Emotional Quotient (EQ), Spiritual Quotient (SQ) with a variety of effective innovation and real-time. With the full day school program, students can avoid all kinds of negative influences outside the school. Full day school supervision of students when parents are busy working, not able to provide good supervision each day, teachers and schools will be taking a big role in the education of children. Full day school students will be able to lead to the formation of personality and character, through habituation-conditioning when students practice the knowledge they have received while staying at the teachers supervision.